PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MEMBELI SMARTPHONE SAMSUNG GALAXY SERIES DI SAMARINDA - Sarwo Eddy W., Lico Thomas, H. Eddy Soegiarto K (EKONOMIA, 2016)
The purpose of this study was to determine the effect of marketing mix consisting of product, price, promotion and place and determine which variables most influence the decision to buy Smartphone Samsung galaxy series in Samarinda. Basic theory used is the marketing management theory by using multiple linear regression analysis. The study population was Samarinda city dwellers who buy Smartphone Samsung galaxy series, while the total sample of 50 respondents. Based on the data analysis is concluded, the following results: As per the F test results showed that the product variable (X1), price (X2), promotion (X3), point (X4), together - together have a significant influence on purchase decisions Smartphone Samsung galaxy series in Samarinda for 2,777 F value calculation result is far greater than the value listed in table F of 2.58 with a coefficient of influence by 19.8% while the remaining 80.2% is determined other factors not dimsaukkan in this research model. When viewed partially shows the effect of each - each variable is as follows: product (X1) = 20.9%, the price (X2) = 08,0%, promotion (X3) = 10.2%, point (X4) = 03.5%